Convergence Analysis of Economic Growth on Sumatra Island - Darwin Damanik (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to determine the level of convergence of economic growth in Sumatra Island from 2015 to 2021. The data used are secondary data sourced from the Central Agency. Statistics. The analysis used in this research is Regression Test Analysis, Partial Test (t-test), and Simultaneous Test (F test). The third model is used to see the level of convergent beta on the island of Sumatra. The results of data analysis show that both per capita PDRB and PDRB growth show the level of convergence that occurs is greater than zero (> 0). This means that the growth of PDRB per capita and PDRB between provinces on the island of Sumatra tends to diverge. Economic growth in poor areas is still relatively slow compared to rich areas. The results of research conducted in 10 provinces on the island of Sumatra for the period 2015-2021 have an absolute convergence speed (economic growth) of 0.587670 which means that there has been a convergence speed of economic growth at absolute convergence on the island of Sumatra.